Environmental factors affecting streambed microplastics in a non-perennial river catchment - Nans Barthelemy; Florian Mermillod-Blondin; Maxime Logez; David Eme; Stefan Krause; Thibault Datry; Laurent Simon (Environmental Research, 2026)

Drying Halves Decomposition Rates in River Networks by Decreasing Decomposer Diversity - Rubén del Campo; Thibault Datry; Arnaud Foulquier; Naiara López‐Rojo; Loïc Chalmandrier; Zoltán Csabai; David Cunillera‐Montcusí; Amaia A. Rodeles; Francisco J. Peñas; Bálint Pernecker; Núria Bonada; José Barquín; et al. (Global Change Biology, 2026)
River drying is intensifying worldwide due to climate change and increasing water abstraction, with major consequences for riverine biodiversity and ecosystem functioning. In river networks, drying not only alters local environmental conditions but also disrupts hydrological connectivity, reshaping the movement of organisms and resources at the river network scale. Leaf litter decomposition—a key ecosystem function in freshwater systems—is particularly sensitive to changes in the structure of decomposer communities. We hypothesized that spatiotemporal patterns of drying regulate decomposition by altering the diversity and composition of detritivorous macroinvertebrates, bacteria and fungi. We combined data from six European river networks spanning a wide latitudinal gradient to assess how local drying intensity and regional hydrological connectivity affect decomposition through changes in these decomposer groups. We found that short drying events (≤ 6 dry days) reduced decomposition rates by up to 50% mainly mediated by changes in the composition and diversity of decomposer communities. Drying decreased the diversity of groups contributing to decomposition, shifting the control of this function from a balanced contribution of fungi, bacteria and detritivores in perennial rivers to dominance by dry‐tolerant but less efficient bacteria in drying rivers. These community shifts persisted for months after flow resumption, causing sustained reductions in decomposition also in flowing conditions. Regional hydrological connectivity alleviated these negative effects of local drying by facilitating the recovery of more efficient aquatic decomposers. However, this effect depended on the river network. In more arid networks, stronger fragmentation hindered the recovery of decomposer communities after flow resumption. Overall, our results evidence that spatiotemporal patterns of drying can regulate the linkages between community structure and ecosystem functioning in river networks. As drying events become more frequent and prolonged, shifts in decomposers' diversity are likely to alter carbon cycling and energy fluxes in freshwater ecosystems under global change.

Hydrological fluctuations determine predator–prey interactions in a semi-arid non-perennial river - Milena Gonçalves-Silva; Elvira D’Bastiani; Thibault Datry; Carla Ferreira Rezende (Hydrobiologia, 2026)

Intermittent rivers in peri‑urban areas act as significant but overlooked sources of N2O emissions - Jiaao Bao; Junfeng Wang; Wenhao Xu; Zhuangzhuang Zhang; Thibault Datry; Lluís Gómez-Gener; Xin Chen; Jie Zhang; Jichen Li; William H. McDowell; Xinghui Xia (Water Research, 2026)

Responses of aquatic communities to seasonal changes in a non-perennial river of the Brazilian semiarid region - Milena Gonçalves-Silva; Thibault Datry; Marcos Adelino Almeida Filho; Maria Rita Nascimento Duarte; Camila Rabelo Oliveira Leal; Tamara Maciel Pereira; Victor Satoru Saito; Andros T. Gianuca; Carla Ferreira Rezende (Aquatic Sciences, 2026)

Exploring the spatio-temporal dynamics of disturbed metacommunities: A mechanistic modeling approach to species resistance and resilience strategies in drying river networks - Lysandre Journiac; Franck Jabot; Claire Jacquet; Annika Künne; Mathis Loïc Messager; Louise Mimeau; Thibault Datry; Núria Bonada; François Munoz; Loïc Chalmandrier (Ecological Modelling, 2025)

Increased assimilation efficiency and mortality rate in Gammarus fossarum exposed to PVC microplastics - Nans Barthelemy; Florian Mermillod-Blondin; Anabelle Espeyte; Mohammad Wazne; Frédéric Hervant; Ghislaine Broillet; Davide Degli-Esposti; Arnaud Chaumot; Stefan Krause; Laurent Simon; Thibault Datry (Environmental Pollution, 2025)

Natural Disturbances and Connectivity Drive Seasonal Taxonomic and Trait Patterns of Aquatic Macroinvertebrate Communities Across Europe - Loïc Chalmandrier; David Cunillera‐Montcusí; Naiara López‐Rojo; Miguel Cañedo‐Argüelles; Zoltán Csabai; Maria Soria; Arnaud Foulquier; Franck Jabot; Marko Miliša; Heikki Mykrä; Petr Pařil; Bálint Pernecker; et al. (Global Ecology and Biogeography, 2025)
Aim Understanding the joint influence of natural disturbance regime, connectivity and biogeography on the seasonal variation of community structure. Location Drying river networks (DRN) in Europe. Time Period Present. Major Taxa Studied Aquatic macroinvertebrates. Methods We analyse the taxonomic and trait structure of 638 macroinvertebrate communities sampled across 125 reaches with perennial and intermittent streamflow, surveyed in six DRNs across Europe, up to six times over 1 year. Results Richness and trait diversity of macroinvertebrate communities decreased with increasing drying frequency, but increased with spatio‐temporal connectivity in reaches with long drying events. Communities experiencing frequent drying events had higher relative abundance of taxa with a long lifecycle and drying resistance traits. Communities experiencing long drying events compensated by high spatio‐temporal connectivity, and had more taxa with high fecundity and high dispersal ability. Taxa richness peaked in summer but that pattern was more prominent when drying frequency was high. Trait diversity decreased throughout the year, showing increasing abiotic stress as the year progressed. Communities changed from communities of mobile, fecund, short‐lived taxa in spring and autumn to communities of long‐lived taxa in summer. However, when drying frequency increased, autumn communities shifted towards communities of long‐lived taxa. Macroinvertebrate community trait structure changed across Europe. It opposed communities from Mediterranean and/or upland DRNs (with more fecund and mobile taxa) to lowland DRNs (with more long‐lived taxa). Main Conclusions Frequency and duration of drying events and spatio‐temporal connectivity drive divergent macroinvertebrate community structures, suggesting the presence of an ecological threshold that explains the variability of disturbed ecosystems across broad spatial scales. These factors also influence seasonal variations, with macroinvertebrate communities shaped by distinct trait‐filtering processes throughout the year based on drying frequency. Ultimately, spatio‐temporal connectivity plays a crucial role in sustaining species richness and trait diversity in reaches experiencing intense drying.

River Drying Causes Local Losses and Regional Gains in Aquatic Invertebrate Metacommunity Diversity: A Cross‐Continental Comparison - Daniel Escobar‐Camacho; Julie Crabot; Rachel Stubbington; Judy England; Romain Sarremejane; Núria Bonada; José María Fernández‐Calero; Miguel Cañedo‐Argüelles; Carla Ferreira Rezende; Pierre Chanut; Zoltán Csabai; Andrea C. Encalada; et al. (Global Change Biology, 2025)
Drying river networks include non‐perennial reaches that cease to flow or dry, and drying is becoming more prevalent with ongoing climate change. Biodiversity responses to drying have been explored mostly at local scales in a few regions, such as Europe and North America, limiting our ability to predict future global scenarios of freshwater biodiversity. Locally, drying acts as a strong environmental filter that selects for species with adaptations promoting resistance or resilience to desiccation, thus reducing aquatic α‐diversity. At the river network scale, drying generates complex mosaics of dry and wet habitats, shaping metacommunities driven by both environmental and dispersal processes. By repeatedly resetting community succession, drying can enhance β‐diversity in space and time. To investigate the transferability of these concepts across continents, we compiled and analyzed a unique dataset of 43 aquatic invertebrate metacommunities from drying river networks in Europe and South America. In Europe, α‐diversity was consistently lower in non‐perennial than perennial reaches, whereas this pattern was not evident in South America. Concomitantly, β‐diversity was higher in non‐perennial reaches than in perennial ones in Europe but not in South America. In general, β‐diversity was predominantly driven by turnover rather than nestedness. Dispersal was the main driver of metacommunity dynamics, challenging prevailing views in river science that environmental filtering is the primary process shaping aquatic metacommunities. Lastly, α‐diversity decreased as drying duration increased, but this was not consistent across Europe. Overall, drying had continent‐specific effects, suggesting limited transferability of knowledge accumulated from North America and Europe to other biogeographic regions. As climate change intensifies, river drying is increasing, and our results underscore the importance of studying its effects across different regions. The importance of dispersal also suggests that management efforts should seek to enhance connectivity between reaches to effectively monitor, restore and conserve freshwater biodiversity.

Hydrological conditions determine the assembly processes of zooplankton in the largest Yangtze River-connected Lake in China - Qingji Zhang; Yongjiu Cai; Qiqi Yuan; Jianghua Yang; Rui Dong; Zhijun Gong; Thibault Datry; Boqiang Qin (Journal of Hydrology, 2024)

River flow intermittence influence biodiversity–stability relationships across spatial scales: Implications for an uncertain future - Andros T. Gianuca; Victor R. di Cavalcanti; Leonardo Cruz; Mathieu Floury; Julie Crabot; Laurent Valette; Jeremy Piffady; Thibault Datry (Global Change Biology, 2024)
Climate change is increasing the proportion of river networks experiencing flow intermittence, which in turn reduces local diversity (i.e., α‐diversity) but enhances variation in species composition among sites (i.e., β‐diversity), with potential consequences on ecosystem stability. Indeed, the multiscale theory of stability proposes that regional stability can be attained not only by local processes but also by spatial asynchrony among sites. However, it is still unknown whether and how scale‐dependent changes in biodiversity associated with river flow intermittence influence stability across spatial scales. To elucidate this, we here focus on multiple metacommunities of French rivers experiencing contrasting levels of flow intermittence. We clearly show that the relative contribution of spatial asynchrony to regional stability was higher for metacommunities of intermittent than perennial rivers. Surprisingly, spatial asynchrony was mainly linked to asynchronous population dynamics among sites, but not to β‐diversity. This finding was robust for both truly aquatic macroinvertebrates and for taxa that disperse aerially during their adult stages, implying the need to conserve multiple sites across the landscape to attain regional stability in intermittent rivers. By contrast, metacommunities of truly aquatic macroinvertebrates inhabiting perennial rivers were mainly stabilized by local processes. Our study provides novel evidence that metacommunities of perennial and intermittent rivers are stabilized by contrasting processes operating at different spatial scales. We demonstrate that flow intermittence enhances spatial asynchrony among sites, thus resulting in a regional stabilizing effect on intermittent river networks. Considering that climate change is increasing the proportion of intermittent rivers worldwide, our results suggest that managers need to focus on the spatial dynamics of metacommunities more than on local‐scale processes to monitor, restore, and conserve freshwater biodiversity.

Unfolding the dynamics of ecosystems undergoing alternating wet‐dry transitional states - Rebeca Arias‐Real; Manuel Delgado‐Baquerizo; Sergi Sabater; Cayetano Gutiérrez‐Cánovas; Enrique Valencia; Gregorio Aragón; Yolanda Cantón; Thibault Datry; Paolo Giordani; Nagore G. Medina; Asunción de los Ríos; Anna M. Romaní; et al. (Ecology Letters, 2024)
A significant fraction of Earth's ecosystems undergoes periodic wet‐dry alternating transitional states. These globally distributed water‐driven transitional ecosystems, such as intermittent rivers and coastal shorelines, have traditionally been studied as two distinct entities, whereas they constitute a single, interconnected meta‐ecosystem. This has resulted in a poor conceptual and empirical understanding of water‐driven transitional ecosystems. Here, we develop a conceptual framework that places the temporal availability of water as the core driver of biodiversity and functional patterns of transitional ecosystems at the global scale. Biological covers (e.g., aquatic biofilms and biocrusts) serve as an excellent model system thriving in both aquatic and terrestrial states, where their succession underscores the intricate interplay between these two states. The duration, frequency, and rate of change of wet‐dry cycles impose distinct plausible scenarios where different types of biological covers can occur depending on their desiccation/hydration resistance traits. This implies that the distinct eco‐evolutionary potential of biological covers, represented by their trait profiles, would support different functions while maintaining similar multifunctionality levels. By embracing multiple alternating transitional states as interconnected entities, our approach can help to better understand and manage global change impacts on biodiversity and multifunctionality in water‐driven transitional ecosystems, while providing new avenues for interdisciplinary studies.

River network‐scale drying impacts the spatiotemporal dynamics of greenhouse gas fluxes - Teresa Silverthorn; Naiara López‐Rojo; Romain Sarremejane; Arnaud Foulquier; Vincent Chanudet; Abdelkader Azougui; Rubén del Campo; Gabriel Singer; Thibault Datry (Limnology and Oceanography, 2024)
Rivers significantly contribute to global biogeochemical cycles; however, we have a limited understanding of how drying may influence these cycles. Drying fragments river networks, thereby influencing important ecosystem functions such as the processing of carbon and nitrogen, and associated fluxes of greenhouse gases (GHGs) both locally, and at the river network scale. Our objective was to assess, using a network‐scale approach, the lateral, longitudinal, and temporal dynamics of GHG fluxes in a river network naturally fragmented by drying. We used a closed‐loop chamber with automated analyzers to measure carbon dioxide (CO 2 ), methane (CH 4 ), and nitrous oxide (N 2 O) fluxes from dry sediments, flowing waters, isolated pools, and riparian soils, along with a suite of environmental variables, over 9 months at 20 sites across a non‐perennial river network in France. Network‐scale drying had a spatial and temporal legacy effect on GHG fluxes. On average, CO 2 fluxes were up to 29 times higher from perennial than non‐perennial sites under flowing conditions. At non‐perennial sites, CO 2 and N 2 O fluxes positively covaried with time since rewetting. In addition, CO 2 and N 2 O fluxes at perennial sites positively covaried with the percent of non‐perennial reaches upstream, indicating a spatial effect of drying. GHG fluxes from riparian soil and dry riverbed sediments had markedly different magnitudes and covariates. This research demonstrates that drying not only has a local‐scale impact but also influences GHG fluxes at the network scale, contributing valuable insights for upscaling global riverine GHG estimates.

Understanding temporal variability across trophic levels and spatial scales in freshwater ecosystems - Tadeu Siqueira; Charles P. Hawkins; Julian D. Olden; Jonathan Tonkin; Lise Comte; Victor S. Saito; Thomas L. Anderson; Gedimar P. Barbosa; Núria Bonada; Claudia C. Bonecker; Miguel Cañedo‐Argüelles; Thibault Datry; et al. (Ecology, 2024)
A tenet of ecology is that temporal variability in ecological structure and processes tends to decrease with increasing spatial scales (from locales to regions) and levels of biological organization (from populations to communities). However, patterns in temporal variability across trophic levels and the mechanisms that produce them remain poorly understood. Here we analyzed the abundance time series of spatially structured communities (i.e., metacommunities) spanning basal resources to top predators from 355 freshwater sites across three continents. Specifically, we used a hierarchical partitioning method to disentangle the propagation of temporal variability in abundance across spatial scales and trophic levels. We then used structural equation modeling to determine if the strength and direction of relationships between temporal variability, synchrony, biodiversity, and environmental and spatial settings depended on trophic level and spatial scale. We found that temporal variability in abundance decreased from producers to tertiary consumers but did so mainly at the local scale. Species population synchrony within sites increased with trophic level, whereas synchrony among communities decreased. At the local scale, temporal variability in precipitation and species diversity were associated with population variability (linear partial coefficient, β = 0.23) and population synchrony (β = −0.39) similarly across trophic levels, respectively. At the regional scale, community synchrony was not related to climatic or spatial predictors, but the strength of relationships between metacommunity variability and community synchrony decreased systematically from top predators (β = 0.73) to secondary consumers (β = 0.54), to primary consumers (β = 0.30) to producers (β = 0). Our results suggest that mobile predators may often stabilize metacommunities by buffering variability that originates at the base of food webs. This finding illustrates that the trophic structure of metacommunities, which integrates variation in organismal body size and its correlates, should be considered when investigating ecological stability in natural systems. More broadly, our work advances the notion that temporal stability is an emergent property of ecosystems that may be threatened in complex ways by biodiversity loss and habitat fragmentation.

The faunal Ponto-Caspianization of central and western European waterways - Ismael Soto; Ross N. Cuthbert; Anthony Ricciardi; Danish A. Ahmed; Florian Altermatt; Ralf B. Schäfer; Gaït Archambaud-Suard; Núria Bonada; Miguel Cañedo-Argüelles; Zoltán Csabai; Thibault Datry; Jaimie T. A. Dick; et al. (Biological Invasions, 2023)
As alien invasive species are a key driver of biodiversity loss, understanding patterns of rapidly changing global species compositions depends upon knowledge of invasive species population dynamics and trends at large scales. Within this context, the Ponto-Caspian region is among the most notable donor regions for aquatic invasive species in Europe. Using macroinvertebrate time series collected over 52 years (1968–2020) at 265 sites across 11 central and western European countries, we examined the occurrences, invasion rates, and abundances of freshwater Ponto-Caspian fauna. We examined whether: (i) successive Ponto-Caspian invasions follow a consistent pattern of composition pioneered by the same species, and (ii) Ponto-Caspian invasion accelerates subsequent invasion rates. In our dataset, Ponto-Caspian macroinvertebrates increased from two species in 1972 to 29 species in 2012. This trend was parallelled by a non-significant increasing trend in the abundances of Ponto-Caspian taxa. Trends in Ponto-Caspian invader richness increased significantly over time. We found a relatively uniform distribution of Ponto-Caspian macroinvertebrates across Europe without any relation to the distance to their native region. The Ponto-Caspian species that arrived first were often bivalves (46.5% of cases), particularly Dreissena polymorpha , followed secondarily by amphipods (83.8%; primarily Chelicorophium curvispinum and Dikerogammarus villosus ) . The time between consecutive invasions decreased significantly at our coarse regional scale, suggesting that previous alien establishments may facilitate invasions of subsequent taxa. Should alien species continue to translocate from the Ponto-Caspian region, our results suggest a high potential for their future invasion success highly connected central and western European waters. However, each species’ population may decline after an initial ‘boom’ phase or after the arrival of new invasive species, resulting in different alien species dominating over time.

Long-term trends in crayfish invasions across European rivers - Ismael Soto; Danish A. Ahmed; Ayah Beidas; Francisco J. Oficialdegui; Elena Tricarico; David G. Angeler; Giuseppe Amatulli; Elizabeta Briski; Thibault Datry; Alain Dohet; Sami Domisch; Judy England; et al. (Science of The Total Environment, 2023)

Clogging modulates the copper effects on microbial communities of streambed sediments - Laura Kergoat; Aymeric Dabrin; Matthieu Masson; Thibault Datry; Chloé Bonnineau (Ecotoxicology, 2023)

“It's dry, it has fewer charms!”: Do perceptions and values of intermittent rivers interact with their management? - Marylise Cottet; Agathe Robert; Hervé Tronchère-Cottet; Thibault Datry (Environmental Science & Policy, 2023)

Invasion impacts and dynamics of a European‐wide introduced species - Phillip J. Haubrock; Danish A. Ahmed; Ross N. Cuthbert; Rachel Stubbington; Sami Domisch; Jaime R. G. Marquez; Ayah Beidas; Giuseppe Amatulli; Jens Kiesel; Longzhu Q. Shen; Ismael Soto; David G. Angeler; et al. (Global Change Biology, 2022)
Globalization has led to the introduction of thousands of alien species worldwide. With growing impacts by invasive species, understanding the invasion process remains critical for predicting adverse effects and informing efficient management. Theoretically, invasion dynamics have been assumed to follow an “invasion curve” (S‐shaped curve of available area invaded over time), but this dynamic has lacked empirical testing using large‐scale data and neglects to consider invader abundances. We propose an “impact curve” describing the impacts generated by invasive species over time based on cumulative abundances. To test this curve's large‐scale applicability, we used the data‐rich New Zealand mud snail Potamopyrgus antipodarum , one of the most damaging freshwater invaders that has invaded almost all of Europe. Using long‐term (1979–2020) abundance and environmental data collected across 306 European sites, we observed that P. antipodarum abundance generally increased through time, with slower population growth at higher latitudes and with lower runoff depth. Fifty‐nine percent of these populations followed the impact curve, characterized by first occurrence, exponential growth, then long‐term saturation. This behaviour is consistent with boom‐bust dynamics, as saturation occurs due to a rapid decline in abundance over time. Across sites, we estimated that impact peaked approximately two decades after first detection, but the rate of progression along the invasion process was influenced by local abiotic conditions. The S‐shaped impact curve may be common among many invasive species that undergo complex invasion dynamics. This provides a potentially unifying approach to advance understanding of large‐scale invasion dynamics and could inform timely management actions to mitigate impacts on ecosystems and economies.

Aquatic organic matter decomposition in the terrestrial environments of an intermittent headwater stream - Nans Barthélémy; Romain Sarremejane; Thibault Datry (Aquatic Sciences, 2022)

Cover Image - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)

A global agenda for advancing freshwater biodiversity research - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)
Global freshwater biodiversity is declining dramatically, and meeting the challenges of this crisis requires bold goals and the mobilisation of substantial resources. While the reasons are varied, investments in both research and conservation of freshwater biodiversity lag far behind those in the terrestrial and marine realms. Inspired by a global consultation, we identify 15 pressing priority needs, grouped into five research areas, in an effort to support informed stewardship of freshwater biodiversity. The proposed agenda aims to advance freshwater biodiversity research globally as a critical step in improving coordinated actions towards its sustainable management and conservation.

Trends in flow intermittence for European rivers - Yves Tramblay; Agnieszka Rutkowska; Eric Sauquet; Catherine Sefton; Gregor Laaha; Marzena Osuch; Teresa Albuquerque; Maria Helena Alves; Kazimierz Banasik; Aurelien Beaufort; Luca Brocca; Stefania Camici; et al. (Hydrological Sciences Journal, 2021)

Assessing metacommunity processes through signatures in spatiotemporal turnover of community composition - Franck Jabot; Fabien Laroche; François Massol; Florent Arthaud; Julie Crabot; Maxime Dubart; Simon Blanchet; François Munoz; Patrice David; Thibault Datry (Ecology Letters, 2020)
Although metacommunity ecology has been a major field of research in the last decades, with both conceptual and empirical outputs, the analysis of the temporal dynamics of metacommunities has only emerged recently and consists mostly of repeated static analyses. Here we propose a novel analytical framework to assess metacommunity processes using path analyses of spatial and temporal diversity turnovers. We detail the principles and practical aspects of this framework and apply it to simulated datasets to illustrate its ability to decipher the respective contributions of entangled drivers of metacommunity dynamics. We then apply it to four empirical datasets. Empirical results support the view that metacommunity dynamics may be generally shaped by multiple ecological processes acting in concert, with environmental filtering being variable across both space and time. These results reinforce our call to go beyond static analyses of metacommunities that are blind to the temporal part of environmental variability.

Simulating rewetting events in intermittent rivers and ephemeral streams: A global analysis of leached nutrients and organic matter - Oleksandra Shumilova; Dominik Zak; Thibault Datry; Daniel von Schiller; Roland Corti; Arnaud Foulquier; Biel Obrador; Klement Tockner; Daniel C. Allan; Florian Altermatt; María Isabel Arce; Shai Arnon; et al. (Global Change Biology, 2019)
Climate change and human pressures are changing the global distribution and the extent of intermittent rivers and ephemeral streams (IRES), which comprise half of the global river network area. IRES are characterized by periods of flow cessation, during which channel substrates accumulate and undergo physico‐chemical changes (preconditioning), and periods of flow resumption, when these substrates are rewetted and release pulses of dissolved nutrients and organic matter (OM). However, there are no estimates of the amounts and quality of leached substances, nor is there information on the underlying environmental constraints operating at the global scale. We experimentally simulated, under standard laboratory conditions, rewetting of leaves, riverbed sediments, and epilithic biofilms collected during the dry phase across 205 IRES from five major climate zones. We determined the amounts and qualitative characteristics of the leached nutrients and OM, and estimated their areal fluxes from riverbeds. In addition, we evaluated the variance in leachate characteristics in relation to selected environmental variables and substrate characteristics. We found that sediments, due to their large quantities within riverbeds, contribute most to the overall flux of dissolved substances during rewetting events (56%–98%), and that flux rates distinctly differ among climate zones. Dissolved organic carbon, phenolics, and nitrate contributed most to the areal fluxes. The largest amounts of leached substances were found in the continental climate zone, coinciding with the lowest potential bioavailability of the leached OM. The opposite pattern was found in the arid zone. Environmental variables expected to be modified under climate change (i.e. potential evapotranspiration, aridity, dry period duration, land use) were correlated with the amount of leached substances, with the strongest relationship found for sediments. These results show that the role of IRES should be accounted for in global biogeochemical cycles, especially because prevalence of IRES will increase due to increasing severity of drying events.

Structural and functional responses of invertebrate communities to climate change and flow regulation in alpine catchments - Daniel Bruno; Oscar Belmar; Anthony Maire; Adrien Morel; Bernard Dumont; Thibault Datry (Global Change Biology, 2019)
Understanding and predicting how biological communities respond to climate change is critical for assessing biodiversity vulnerability and guiding conservation efforts. Glacier‐ and snow‐fed rivers are one of the most sensitive ecosystems to climate change, and can provide early warning of wider‐scale changes. These rivers are frequently used for hydropower production but there is minimal understanding of how biological communities are influenced by climate change in a context of flow regulation. This study sheds light on this issue by disentangling structural (water temperature preference, taxonomic composition, alpha, beta and gamma diversities) and functional (functional traits, diversity, richness, evenness, dispersion and redundancy) effects of climate change in interaction with flow regulation in the Alps. For this, we compared environmental and aquatic invertebrate data collected in the 1970s and 2010s in regulated and unregulated alpine catchments. We hypothesized a replacement of cold‐adapted species by warming‐tolerant ones, high temporal and spatial turnover in taxa and trait composition, along with reduced taxonomic and functional diversities in consequence of climate change. We expected communities in regulated rivers to respond more drastically due to additive or synergistic effects between flow regulation and climate change. We found divergent structural but convergent functional responses between free‐flowing and regulated catchments. Although cold‐adapted taxa decreased in both of them, greater colonization and spread of thermophilic species was found in the free‐flowing one, resulting in higher spatial and temporal turnover. Since the 1970s, taxonomic diversity increased in the free flowing but decreased in the regulated catchment due to biotic homogenization. Colonization by taxa with new functional strategies (i.e. multivoltine taxa with small body size, resistance forms, aerial dispersion and reproduction by clutches) increased functional diversity but decreased functional redundancy through time. These functional changes could jeopardize the ability of aquatic communities facing intensification of ongoing climate change or new anthropogenic disturbances.

Interpreting beta‐diversity components over time to conserve metacommunities in highly dynamic ecosystems - Albert Ruhí; Thibault Datry; John L. Sabo (Conservation Biology, 2017)
The concept of metacommunity (i.e., a set of local communities linked by dispersal) has gained great popularity among community ecologists. However, metacommunity research mostly addresses questions on spatial patterns of biodiversity at the regional scale, whereas conservation planning requires quantifying temporal variation in those metacommunities and the contributions that individual (local) sites make to regional dynamics. We propose that recent advances in diversity‐partitioning methods may allow for a better understanding of metacommunity dynamics and the identification of keystone sites. We used time series of the 2 components of beta diversity (richness and replacement) and the contributions of local sites to these components to examine which sites controlled source‐sink dynamics in a highly dynamic model system (an intermittent river). The relative importance of the richness and replacement components of beta diversity fluctuated over time, and sample aggregation led to underestimation of beta diversity by up to 35%. Our literature review revealed that research on intermittent rivers would benefit greatly from examination of beta‐diversity components over time. Adequately appraising spatiotemporal variability in community composition and identifying sites that are pivotal for maintaining biodiversity at the landscape scale are key needs for conservation prioritization and planning. Thus, our framework may be used to guide conservation actions in highly dynamic ecosystems when time‐series data describing biodiversity across sites connected by dispersal are available.

Invertebrate assemblage responses and the dual roles of resistance and resilience to drying in intermittent rivers - Catherine Leigh; Núria Bonada; Andrew J. Boulton; Bernard Hugueny; Scott T. Larned; Ross Vander Vorste; Thibault Datry (Aquatic Sciences, 2016)

A comparison of pitfall-trap and quadrat methods for sampling ground-dwelling invertebrates in dry riverbeds - Roland Corti; Scott T. Larned; Thibault Datry (Hydrobiologia, 2013)

Benthic and hyporheic invertebrate assemblages along a gradient of increasing streambed colmation by fine sediment - Stephane Descloux; Thibault Datry; Pierre Marmonier (Aquatic Sciences, 2013)

Recent perspectives on temporary river ecology - Thibault Datry; David B. Arscott; Sergi Sabater (Aquatic Sciences, 2011)

Flow intermittence controls leaf litter breakdown in a French temporary alluvial river: the “drying memory” - Thibault Datry; R. Corti; C. Claret; M. Philippe (Aquatic Sciences, 2011)

Invertebrate and microbial responses to inundation in an ephemeral river reach in New Zealand: effects of preceding dry periods - Scott T. Larned; Thibault Datry; Christopher T. Robinson (Aquatic Sciences, 2007)